An investigation of the relationship between advertising and television programming and programmes on South African television - Sikhakhane, Mongezi Andrew (My University, 2007)
This research report forms part of current debates in media studies around the rapidly increasing commercialization and privatization of public broadcasters around the world. It investigates the impact of this commercialization and privatization on the role of these broadcasters. It looks at some impacts that the dependence of public broadcasters on advertising has on their roles public service roles. South Africa is not immune from these global trends that are mentioned above. As suggested by the ICASA, the government reduced its funding of the public broadcaster (SABC). This forced the SABC to rely more and more on income from advertising and various forms of sponsorship in order to sustain and fulfill its goals. This research provides an investigation and findings of the nature and extent of the impact of advertising influence on both the SABC and to some extent E-TV programming and programmes. This study is important because it covers an important area since it looks at the rapid changes taking place in the funding and the content of local television (South African Television). It will make both a theoretical and empirical contribution to the understanding of trends and developments that are taking place in South African Television. It is comprised of three chapters with each treating its own theme ranging from policy and literature analysis, news and drama programme analysis and finally a case study, which provides an analysis of first hand information from the SABC officials from both the programming and the advertising department.
Student Number : 9609557F - Master of Journalism and Media Studies research report - Faculty of Humanities
Keywords: public broadcasters; commercialization; privatization; South Africa; SABC; E-TV; South African Television